The Mediating Role of Physical Literacy in the Relationship Between e-Health Literacy and a Sustainable Healthy Lifestyle Among Adolescents - Akarsu, Mehmet; Gullu, Mehmet; Gunata, Gul Polat; Kizilkaya, Aysel; Aydin, Savas; Ozcan, Ecesu; Kurhan, Cihad Onur (Mdpi, 2025)
Background: It is well-established that, for adolescents to adopt sustainable healthy lifestyle behaviors, not only access to information but also the skills required to translate that information into action are critical. In this field, research that examines the relationship between e-health literacy and sustainable healthy lifestyle behaviors within the context of physical literacy is notably scarce. In this context, the aim of this study is to examine the effect of e-health literacy on a sustainable healthy lifestyle and to evaluate the mediating role of physical literacy in this relationship. Methods: A total of 835 adolescents from high schools across T & uuml;rkiye voluntarily participated in this study. During the data collection process, the e-Health Literacy Scale, the Perceived Physical Literacy Scale, and the Healthy and Sustainable Lifestyle Scale were utilized. Data were analyzed using the JASP (version 0.18.3.0) software. Correlation analysis and structural equation modeling were conducted, and the bootstrap method (n = 5000) was employed for mediation analysis. Results: The effect of e-health literacy on a sustainable healthy lifestyle was found to be positive and statistically significant (beta = 0.452, p < 0.001). Similarly, e-health literacy significantly predicted physical literacy (beta = 0.755, p < 0.001), and physical literacy significantly predicted a sustainable healthy lifestyle (beta = 0.310, p < 0.001). The mediating effect was also statistically significant (beta = 0.234, p < 0.001). The model explained 32% of the variance in healthy lifestyle behaviors. Conclusions: The findings indicate that evaluating e-health literacy and physical literacy together provides a holistic approach to fostering sustainable healthy lifestyle habits among adolescents. It is recommended that intervention programs be structured to encompass both areas of competence.
Keywords: e-health literacy; physical literacy; sustainable healthy lifestyle; adolescents; health behaviors; health education; mediation model